RoboPol: AGN polarimetric monitoring data. Issue 3 (16th December 2020) - Blinov, D; Kiehlmann, S; Pavlidou, V; Panopoulou, G V; Skalidis, R; Angelakis, E; Casadio, C; Einoder, E N; Hovatta, T; Kokolakis, K; Kougentakis, A; Kus, A; et al.
ABSTRACT: We present uniformly reprocessed and re-calibrated data from the RoboPol programme of optopolarimetric monitoring of active galactic nuclei (AGNs), covering observations between 2013, when the instrument was commissioned, and 2017. In total, the data set presented in this paper includes 5068 observations of 222 AGN with Dec. > −25 ○ . We describe the current version of the RoboPol pipeline that was used to process and calibrate the entire data set, and we make the data publicly available for use by the astronomical community. Average quantities summarizing optopolarimetric behaviour (average degree of polarization, polarization variability index) are also provided for each source we have observed and for the time interval we have followed it.